Beyond physical accessibility: a bibliometric analysis about the influence of digital communication and the use of technology on inclusive tourism in WCAG 3.0 era—tourism for all from a more accessible content perspective - Fernández-Díaz, Elena (2025)
This study aims to analyze the impact of digital communication and the use of technology in tourism. It also evaluates how new digital and technological trends, such as mobile applications and emerging virtual or augmented reality technologies, can be applied to web pages. Information that is not accessible becomes another barrier for travelers with disabilities and does not contribute to the concept of "tourism for all." A bibliometric analysis through Web of Science (WoS) of published articles related to the influence of digital communication and the use of technology in tourism. A total of 290 articles were analysed using VOSviewer and SciMAT. The web accessibility does contemplate the regulations currently in force and therefore progress continues to be slow in this aspect. Also, technology together with new digital communication channels improve the experience of tourists and visitors to a destination, in turn impacting on their quality of life and enhancing "Tourism for all". Furthermore, it is determined that the "phygital" concept takes on special relevance since many studies are aimed at combining both dimensions so that if a space complies with accessibility regulations, they are also considered from the information point of view in its digital sphere. This study provides an evolution of digital accessibility from a technological and communicational perspective by combining two complementary analyses and allows us to understand tourist behavior from a more inclusive aspect. There are important gaps in other areas of study, especially focused on stakeholders' knowledge of the importance of making improvements in tourism for all.